In-silico tuning of the nano-bio interface by molecular dynamics method: Amyloid beta targeting with two-dimensional metal-organic frameworks - Si Yuanlei; Jokar, Zahra; Khedri, Elham; Khanaman, Parisa Mohammadi; Mohammadgholian, Maryam; Ghotbi, Mahbubeh; İnç, Mustafa (Elsevier Sci Ltd, 2023)
Alzheimer's disease (AD) is the most common type of neurodegenerative disorder. Since these deposits are disease's hallmarks, detecting and preventing them would be excellent assistance for early interventions and slowing down natural course of this ailment. In this work, using atomistic investigation, effectiveness of two-dimensional Metal-organic Frameworks (MOFs) in preventing amyloid formation was studied. Besides, molec-ular dynamic simulation (MD) novel approach of morphological engineering for 2D-MOFs was carried out to inhibit amyloid formation. Although all offered nanoparticles interfered with fibrillation of proteins (UiO-66, IRMOF-16, HKUST-1, and ZIF-8), it was revealed that UiO-66 monolayer presents the highest absolute energy values, the lowest contact level of amyloid particles, the highest number of hydrogen bonds between amyloid molecules and water, the most instability caused in amyloid beta (A beta) particles, and the most significant decrement in compactness of A beta proteins. So, it was concluded that MOFs, especially UiO-66, is capable of preventing amyloid formation and can be promising in treating Alzheimer's Disease. Furthermore, MOFs are highly tuneable, and their features can be attuned to have the maximum contribution in preventing amyloid formation. Finally, by using microfluidic and non-microfluidic methods, an attempt has been made to synthesize a new combination using the UiO-66 and PLGA-PEG.
Keywords: Nanomedicine; Metal-organic frameworks; Molecular dynamic simulation; Microfluidic; Amyloid formation; Alzheimer?s disease